STUDI PERBANDINGAN HASIL SINTESIS METIL-N(2,3-XILIL)ANTRANILAT DENGAN PEREAKSI DIAZOMETANA DAN BF3-METANOL - Gunawan, I W. G. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 1 Januari 2009, 2012)
N(2,3-xylyl)antranilic acid is an analgesic drug which works by inhibiting synthesis of prostaglandin. Through this mechanism N- (2,3-xylyl)antranilic acid causes gastro iritation. Therefore, this research aims to synthesise N- (2,3-xylyl)antranilic ester derivatives using BF3-methanol and diazomethane methods, and to find which methods will give the best result. Diazomethane used for methylation reaction needs to be fresh because it is an unstable gas, while BF3- methanol needs refluxing for 10-15 hours. The physico chemical properties of methylation product were characterised using colour reaction testing, melting point, and Rf value, while the structure was identified using UVvis, FT-IR and 1HNMR. It was found that diazomethane method gave better yield (68%) compared to BF3-methanol (52%). N- (2,3- xylyl)antranilic methyl ester obtained using both methods was found as a yellowish-white shiny crystal having the same degree of purity. In addition, both product revealed the same physico chemical properties such as melting point, colour, and Rf value. Hence, the products obatined using both methods were identical which was N- (2,3- xylyl)antranilic methyl ester.
Keywords: Methyl N(2,3-xylyl) antranilic, diazomethane, BF3-methanol